2008
DOI: 10.1074/jbc.m803646200
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Tyrosine Phosphatase β (RPTPβ) Activity and Signaling Are Attenuated by Glycosylation and Subsequent Cell Surface Galectin-1 Binding

Abstract: O-Mannosyl-linked glycosylation is abundant within the central nervous system, yet very few glycoproteins with this glycan modification have been identified. Congenital diseases with significant neurological defects arise from inactivating mutations found within the glycosyltransferases that act early in the O-mannosyl glycosylation pathway. The N-acetylglucosaminyltransferase known as GnT-Vb or -IX is highly expressed in brain and branches O-mannosyl-linked glycans. Our results using SH-SY5Y neuroblastoma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
87
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 61 publications
(71 reference statements)
4
87
0
Order By: Relevance
“…The conclusion from these experiments was that there was little overall change in the total amount of O-Man glycans when ␣-dystroglycan was not expressed, suggesting that the majority of this class of glycans is actually found expressed on glycoproteins other than ␣-dystroglycan. Our previous in vitro experiments identified RPTP as a potential target of the O-mannosylation pathway (48). Here, we provide the first in vivo evidence that RPTP is indeed a physiological substrate of the O-mannosylation pathway.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…The conclusion from these experiments was that there was little overall change in the total amount of O-Man glycans when ␣-dystroglycan was not expressed, suggesting that the majority of this class of glycans is actually found expressed on glycoproteins other than ␣-dystroglycan. Our previous in vitro experiments identified RPTP as a potential target of the O-mannosylation pathway (48). Here, we provide the first in vivo evidence that RPTP is indeed a physiological substrate of the O-mannosylation pathway.…”
Section: Discussionmentioning
confidence: 56%
“…We show that Cat-315 reactivity detects the elaboration of O-mannosyl glycans on RPTP and that this reactivity is reduced in knock-out animals. The in vitro studies showed that overexpressing GnT-Vb in neuroblastoma cells resulted in altered association of RPTP on the cell surface, which inhibited its phosphatase activity, resulting in destabilized E-cadherin and inhibition of cell-cell adhesion, measured by either aggregation or migration assays (48). It will be interesting to determine whether other members of the RPTP family express O-Man glycans and if their functions are altered when specific O-Man glycans are deleted or overexpressed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations